2015
DOI: 10.1111/jsr.12304
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of automated quantification of motor activity in REM sleep behaviour disorder

Abstract: SUMMARYRapid eye movement (REM) sleep behaviour disorder (RBD) is characterized by dream enactment and REM sleep without atonia. Atonia is evaluated on the basis of visual criteria, but there is a need for more objective, quantitative measurements. We aimed to define and optimize a method for establishing baseline and all other parameters in automatic quantifying submental motor activity during REM sleep. We analysed the electromyographic activity of the submental muscle in polysomnographs of 29 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 24 publications
(36 reference statements)
3
35
0
Order By: Relevance
“…Our group has recently published a study with the aim of finding the most sensitive baseline for measuring EMG activity during REM sleep. 47 However, such a baseline should also be developed when analyzing the whole sleep period, taking into account possible changes in muscular tone across the sleep stages.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has recently published a study with the aim of finding the most sensitive baseline for measuring EMG activity during REM sleep. 47 However, such a baseline should also be developed when analyzing the whole sleep period, taking into account possible changes in muscular tone across the sleep stages.…”
Section: Discussionmentioning
confidence: 99%
“…This was then used to derive features that depict the number of motor activity events, quantified by duration and percentage of REM epochs, to distinguish RBD from other individuals. Despite the abundance of studies on RBD detection, these objective metrics have been applied to relatively small RBD cohorts to date (ranging from 10 to 31 patients), achieving variable sensitivity and specificity (0.74-1.00 and 0.71-1.00, respectively) (Burns et al 2007;Ferri et al 2008Ferri et al , 2010Kempfner et al 2013b;Frauscher et al 2014;Kempfner et al 2014;Frandsen et al 2015). In a preliminary study we showed that using an ensemble of established techniques improved RBD detection, and can be further enhanced with the incorporation of sleep architectural features (Cooray et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For RBD detection, several automated algorithms have been proposed (Ferri et al., , ; Frandsen et al., ; Frauscher et al., ; Kempfner & Nikolic, ; Mayer et al., ) and compared (Cesari et al., ). The algorithm described in Frauscher et al.…”
Section: Discussionmentioning
confidence: 99%
“…For RBD detection, several automated algorithms have been proposed (Ferri et al, 2008(Ferri et al, , 2010Frandsen et al, 2015;Frauscher et al, 2014;Kempfner & Nikolic, 2014;Mayer et al, 2008) and compared . The algorithm described in Frauscher et al (2014) has been recently applied to a big dataset (Haba-rubio et al, 2018), but a formal validation on this dataset is lacking.…”
Section: T-stat P-value T-stat P-value T-stat P-valuementioning
confidence: 99%
See 1 more Smart Citation